Functional characterization of a terpene synthase responsible for (E)-β-ocimene biosynthesis identified in Pyrus betuleafolia transcriptome after herbivory - Huang, Xinzheng; Zhang, Hang; Li, Huali; Wang, Mengting; Guo, Xinyue; Liu, Enliang; Han, Xiaoqiang; Zhen, Congai; Li, Aili; Shi, Wangpeng; Zhang, Yongjun (Frontiers in Plant Science, 2022)
(E)-β-ocimene, a ubiquitous monoterpene volatile in plants, is emitted from flowers to attract pollinators and/or vegetative tissues as part of inducible defenses mediated by complex signaling networks when plants are attacked by insect herbivores. Wild pear species Pyrus betuleafolia used worldwide as rootstock generally displays valuable pest-resistant traits and is a promising genetic resource for pear breeding. In the current study, transcriptional changes in this wild pear species infested with a polyphagous herbivore Spodoptera litura and the underlying molecular mechanisms were fully investigated. A total of 3,118 differentially expressed genes (DEGs) were identified in damaged pear leaf samples. Spodoptera litura larvae infestation activated complex phytohormonal signaling networks in which jasmonic acid, ethylene, brassinosteroids, cytokinin, gibberellic acid and auxin pathways were induced, whereas salicylic acid and abscisic acid pathways were suppressed. All DEGs associated with growth-related photosynthesis were significantly downregulated, whereas most DEGs involved in defense-related early signaling events, transcription factors, green leaf volatiles and volatile terpenes were significantly upregulated. The PbeOCS (GWHGAAYT028729), a putative (E)-β-ocimene synthase gene, was newly identified in P. betuleafolia transcriptome. The upregulation of PbeOCS in S. litura-infested pear leaves supports a potential role for PbeOCS in herbivore-induced plant defenses. In enzyme-catalyzed reaction, recombinant PbeOCS only utilized geranyl pyrophosphate but not neryl diphosphate, farnesyl pyrophosphate or geranylgeranyl diphosphate as a substrate, producing (E)-β-ocimene as the major product and a trace amount of (Z)-β-ocimene. Moreover, as a catalytic product of PbeOCS, (E)-β-ocimene showed repellent effects on larvae of S. litura in dual-choice bioassays. What is more, (E)-β-ocimene increased mortalities of larvae in no-choice bioassays. These findings provide an overview of transcriptomic changes in wild pears in response to chewing herbivores and insights into (E)-β-ocimene biosynthesis in pear plants, which will help elucidate the molecular mechanisms underlying pear-insect interactions.